2002
DOI: 10.1097/00005537-200205000-00023
|View full text |Cite
|
Sign up to set email alerts
|

Nonsurgical Management of Parapharyngeal Space Infections: A Prospective Study

Abstract: Our results confirm the effectiveness of nonsurgical treatment of infections limited to the parapharyngeal space, at least in the pediatric population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
72
0
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(78 citation statements)
references
References 17 publications
2
72
0
4
Order By: Relevance
“…Parapharyngeal infection remains potentially dangerous because of the possibility of severe complications [2] . The treatment options vary between immediate surgical drainage of the abscess to instituting a trial of intravenous antibiotics in every stable case or in selected cases [3,[5][6][7] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Parapharyngeal infection remains potentially dangerous because of the possibility of severe complications [2] . The treatment options vary between immediate surgical drainage of the abscess to instituting a trial of intravenous antibiotics in every stable case or in selected cases [3,[5][6][7] .…”
Section: Discussionmentioning
confidence: 99%
“…Since De Marie et al [4] reported a nonsurgical approach in treating parapharyngeal space infection using intravenous antibiotics and CT-guided selective aspiration, there has been much argument over the criteria for surgical intervention of this disease. Although Sethi and Stanley [8] reported that early open surgical drainage resulted in rapid recovery and short hospital stay, several reports have described changing trends in deep neck space abscesses over time [2][3][4][5] . Sichel et al [2] performed a prospective study of 12 patients with the diagnosis of parapharyngeal infection.…”
Section: Discussionmentioning
confidence: 99%
“…Ekşioğlu et al (14) also highlighted the importance of using neck CT for the management of pediatric deep neck abscess based on its contributions to the ascertainment of complications. Some authors also utilized MRI for complementary diagnostic information (9,15). Despite the fact that CT is responsible for an intense radiation exposure, the long duration and necessity of immobilization during the MRI process and the reductive fine tuning of the radiation dose when performing CT in children in our university limited the preference of MRI in our research.…”
Section: Discussionmentioning
confidence: 99%
“…Vieria et al (16) suggested the use of empirical antibiotics for DNI which have adequate spectrum for both aerobic and anaerobic bacteria such as penicillin alone or combined with beta-lactamase agents, beta-lactamase--resistant drugs such as ceftriaxone, and antibiotics against anaerobic bacteria such as metronidazole and clindamycin. The complete achievement was obtained in a prospective study performed in seven pediatric deep neck abscess cases using amoxicillin and clavulanic acid combination by Sichel et al (15). Lawrence and Bateman (2) determined the recommendation level of the utilization of these antibiotics mentioned above as grade C in their data collection but mostly because of the included reviews' low level of evidence.…”
Section: Discussionmentioning
confidence: 99%
“…Even if some recent reports [1,4,5] have confirmed that intravenous antibiotic therapy alone, associated with strict radiological follow-up, can be successfully used in the management of uncomplicated parapharyngeal abscess, surgical drainage is the treatment of choice in cases where patients are not responsive to first-line antibiotics, with systemic symptoms or with severe complications, such as airway compromise, meningitis, mediastinitis (through retropharyngeal space) and Lemierre's syndrome [6,7]. Following these indications, we decided to promptly perform intraoral drainage in our patient, since he did not respond to the antibiotic therapy, and had episodes of high fever.…”
Section: Discussionmentioning
confidence: 99%